Epidemiological and clinical characteristics of fatalities from COVID-19 in Saudi Arabia: A multicentric, retrospective study - Alahmari, Ahmed; Alowais, Jalal; Khan, Anas (Journal of Nature and Science of Medicine, 2021)
Background: Although Saudi Arabia harbors a large number of confirmed cases with coronavirus disease 2019 (COVID-19), the Kingdom is characterized by a low case fatality rate, compared to that of other parts of the world. Patient-specific factors can play a role in this observation. Thus, we conducted the present retrospective study to investigate the epidemiologic characteristics of all fatalities resulting from COVID-19 infection in Saudi Arabia as of April 27, 2020. Materials and Methods: The present study was a multicentric, retrospective study that retrieved the data of all confirmed COVID-19-related deaths in Saudi Arabia from March 2 to April 27, 2020. Only records of the cases who underwent reverse transcription-polymerase chain reaction laboratory tests to confirm the presence of COVID-19 were retrieved. The data of COVID-19 fatalities in Saudi Arabia were obtained from the Health Electronic Surveillance Network of the Ministry of Health. Results: Up to April 27, 2020, 147 cases of COVID-19-related deaths were reported in Saudi Arabia. Almost two-thirds of them were aged above 50 years and majority of them were male (83.7%). Health-care workers represented 3.1% of the dead cases (n = 4 cases). The vast majority of the cases were from Makkah (44.9%) and Madinah (21.8%). Among males, the number of Saudi cases was much lower than non-Saudi cases with 22 and 101 deaths, respectively. Over 80% of the included cases had reported signs and symptoms before death, mainly fever and cough. Out of the 129 cases who had available data regarding comorbidities, 104 cases (80.6%) had one or more comorbidities. The median (interquartile range [IQR]) time from the onset of symptoms till test result confirmation was 5.5 (5) days, while the median (IQR) time from sample collection till test result confirmation was 1 (2) day. On the other hand, the median time from symptom onset till hospitalization and that till death was 1 (3) and 7 (8) days, respectively. Conclusion: COVID-19 is a growing pandemic with unprecedented spread rate and profound impact on the health of specific subsets of affected patients. In the present report, we demonstrated that fatalities from COVID-19 in Saudi Arabia are more common in older age groups, male patients, and non-Saudi residents. Besides, the presence of comorbidities is highly prevalent among fatalities from COVID-19 in Saudi Arabia. The Saudi health-care system has the advantage of fast-track diagnosis, which, in return, could have contributed to the low case fatality rate observed in the Kingdom. Further studies are required to identify the independent predictors of mortality for patients with COVID-19.